Cost object determination training to support Go-Barber business innovation in Malang City - Putu Indrajaya Lembut; Fitri Oktariani; Yuswanto Yuswanto (University of Merdeka Malang, 2022)
In order to save small business owners, accounting is one of the spearheads that plays a role in maintaining cost efficiency so that service prices can still compete with similar businesses, reducing waste (improvident). Innovation from permanent barber to Go-Barber is should be accompanied by a change in the method of determining the cost object in determining activity cost rates, with additional considerations for measuring services that generally have to pay attention to distance to customers, so that it has an impact on the emergence of variable costs as a basis determine the price of the service. The circle method is considered the right method because it is based on the characteristics of innovation that efforts to innovate will certainly not stop at a certain point, but will continue to evaluate and innovate in response to developments in the business environment. Measurement of the cost object is needed to determine the price of the service based on the basic tariff which will be multiplied by the activity. Identification of the right cost object will provide accuracy in determining the Cost of Goods Sold (COGS) which is of course a method in determining the price of services. Based on the results of training from business actors carried out by instructors/presenters, participants understand enough about how to identify and analyze activity costs to determine the selling price of Go-Barber services where previously there was no calculation method applied by Go-Barber.